Weed Interference on Growth and Leaf Nutrient Accumulation in Two Cassava Varieties - Moratelli, Gustavo; Ferreira, Silvio Douglas; Canavessi, Hiago; Fey, Emerson; Rangel, Marcos Antonio Sedrez; Costa, Neumarcio Vilanova da (Journal of Agricultural Studies, 2021)
The development of cassava varieties with more efficient nutrient absorption can prevent losses caused by weed competition. The objective of this study was to evaluate dry matter accumulation and leaf nutrient content in traditional and improved cassava varieties, with and without coexistence with weeds throughout the cycle. A randomized complete block design was used in a 2 x 2 x 11 factorial scheme with four replications. The first factor consisted of two varieties (Baianinha and Clone 56-03); the second factor was composed of the conditions with and without coexistence with weeds, and the third factor was 11 harvest periods. Coexistence with weeds reduced leaf contents of N (20.8% and 24.8%), P (26.7% and 4.6%) and K (27.1% and 12.6%) for 'Baianinha' and 'Clone 56-03', respectively. For coexistence with 'Baianinha', the period up to the maximum daily nutrient accumulation rate (N, P and K) ranged from 82 to 99 days after planting (DAP), while for 'Clone 56-03', coexistence in this period ranged from 80 to 88 DAP. The plants from the variety 'Clone 56-03' presented higher total dry mass and root dry mass accumulation, as well as higher leaf contents of N, P and K than the traditional cassava variety 'Baianinha', especially when in coexistence with weeds during the whole cycle.